Who Is the Note-Worthy Fan? Featuring Players in the Official Facebook Communication of Mainstream Video Games - Švelch, Jan; Krobová, Tereza (Replay. The Polish Journal of Game Studies, 2017)
Video game fans participate in the official promotion of video games, either voluntarily, or unwillingly when their fanworks are appropriated and used by video game publishers. The article provides a quantitative overview of the presence of fans in the official social media profiles of four selected mainstream games (Dragon Age: Inquistion, Evolve, Mortal Kombat X and The Witcher 3: Wild Hunt) during a one-year period from August 2014 to July 2015. Combining the traditional method of content analysis and Facebook data-mining, we explore the frequency with which fans appear in social media (including questions of various forms of fanworks and gender) and what user activity is generated by posts featuring fans and fan creations. Results show that fans or their fanworks are featured in 8–24% of all posts depending on a game and in the most common categories of painting and cosplay they generate a comparable level of user engagement as traditional promotional posts.